Ecology in the light of biological field conception - Dyk, Wiesław (Studia Ecologiae et Bioethicae, 2005)
Ecology is the interdisciplinary science, so that the analysises carried out in this area shoul include the state of knowledge not only about nature but also humanistic one. The accepted philosophical perspective, general conceptions of science, world, life and human have strong influence on thesises and conclusions. The basises of this article are the Sedlak's conception of biologic field and creativity as one of human features.